Assessing the Implementation of ACTIP in Combating Child Trafficking: A Comparative Study of Indonesia, Malaysia, and Vietnam - Abdurrakhman Alhakim; Mimi Sintia Mohd Bajury; Winsherly Tan; Hanifah Ghafila Romadona; Tantimin Tantimin (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
Child trafficking has continued to happen in Southeast Asia despite the ratification of ACTIP for ASEAN members like Indonesia, Malaysia, and Vietnam. This prompts the need for an assessment of ACTIP enforceability, which is a research gap that has remained underexplored. The ACTIP benchmarking and the focus on Indonesia, Malaysia, and Vietnam serve as the core novelty of this study, with the objective of assessing ACTIP standards and their enforceability in the said ASEAN member states. Findings show that Indonesia has normative disharmony and lacks a clear basis for victim-identification mechanisms. Malaysia demonstrates stronger alignment but retains serious loopholes around marriage, adoption, parental consent, and limited immunity. Vietnam provides stronger victim-support mechanisms but suffers from conflicting age thresholds and problematic non-punishment protection. In response, this study devises practical recommendations for each jurisdiction, with Indonesia recommended to focus on harmonizing its trafficking and child-protection frameworks, Malaysia to remove said loopholes while expanding non-punishment protection, and Vietnam to prioritize aligning its Penal Code with ACTIP’s under-18 standard. This study contribute to the literature on ASEAN anti-trafficking law by showing that ACTIP compliance must be assessed not only through ratification, but also through the domestic legal mechanisms required to make its standards enforceable